What role does mindfulness play in regulating fear of COVID-19 and associated mental health? The results of a cross-sectional study - Lee, Kunhua; Lee, Yu-Xuan; Cheng, Yu-Tung (Frontiers in Psychology, 2023)
Objectives The pandemic has greatly impacted people’s lives and mental health. Therefore, it is now especially important to help people maintain good mental health. The positive effects of mindfulness-based practices on mental health have been demonstrated previously. However, no consensus has yet been reached on the potential mechanisms of mindfulness. This study adopted the two-component model of mindfulness to explain the relationships between fear of COVID-19, and mental health. We proposed the following hypothetical model: (1) fear of COVID-19 could affect orientation to experience; (2) orientation to experience could affect mental health. Directly; (3) fear of COVID-19 could mental health directly; (4) orientation to experience could be a mediator between fear of COVID-19 and mental health. Methods We conducted an online survey in the present study. Three hundred and forty-four respondents were recruited to participate in the present study. After informed consent, they completed the questionnaires on the websites. The participants were asked to complete a questionnaire including the Beck Depression Inventory-II, Beck Anxiety Inventory, the Taiwan version of the Five Facet Mindfulness Questionnaire, and the Fear of COVID-19 Scale. Descriptive analysis and structural equation modeling were used to analyze the data and examine the goodness-of-fit indices. Results Our results not only showed orientation to experience playing as a mediator between fear of COVID-19 and mental health; but also confirmed the roles of nonjudgment and nonreactivity in regulating emotions. Conclusion Experimentation and longitudinal study could be applied to examine the roles of nonjudgment and nonreactivity in the future.